Once and future partners the United States, Russia, and nuclear non-proliferation - Potter, William C.; Bidgood, Sarah (Adelphi (Series) (International Institute for Strategic Studies), 2018)
"This Adelphi book reaches back to episodes of US-Soviet cooperation on nuclear non-proliferation to idenfify factors that permitted successful joint action, even in circumstances of profound geopolitical rivalry. It includes essays on the collaboration that prevented South Africa from conducting a nuclear-weapon test in 1977; Cold War era discussions on peaceful nuclear explosions and the developments that led from the Limited Test-Ban Treaty to the Treaty on the Non-Proliferation of Nuclear Weapons (Non-Proliferation Treaty, or NPT); negotiating and sustaining the NPT; the establishment of the London Club and nuclear-export controls; bolstering IAEA safeguards; and negotiating the draft Radiological Weapons Convention." -- from back cover.